Susceptibility of Caribbean Brain Coral Recruits to Stony Coral Tissue Loss Disease (SCTLD) - Williamson, Olivia M.; Dennison, Caroline E.; O’Neil, Keri L.; Baker, Andrew C. (Frontiers in Marine Science, 2022)
Stony coral tissue loss disease (SCTLD) has devastated coral populations along Florida’s Coral Reef and beyond. Although widespread infection and mortality of adult colonies have been documented, no studies have yet investigated the susceptibility of recruits to this disease. Here, we subjected eight-month-old Diploria labyrinthiformis recruits and four-month-old Colpophyllia natans recruits to two sequential exposures to SCTLD in the laboratory to track infection and assess potential resilience. Both species began to develop lesions as early as 48 h after exposure began. During the first exposure, 59.6% of C. natans recruits lost all tissue (died) within two to eight days of developing lesions, whereas D. labyrinthiformis recruits experienced slower tissue loss and minimal eventual mortality. In C. natans, larger recruits and those fused into groups of multiple genets (chimeras) exhibited the highest survivorship. In contrast, smaller and/or single (ungrouped) recruits had the lowest survivorship (9.9 - 24.8%). After 20 days, a second SCTLD exposure was delivered to further test resistance in remaining recruits, and all recruits of both species succumbed within six days. Although no recruits showed absolute resistance to SCTLD following repeated exposures, our results provide evidence that interactions between size and chimerism can impact relative resistance in C. natans. This study represents the first report of SCTLD in Caribbean coral recruits and carries implications for natural species recovery and reef restoration efforts. Additional research on the susceptibility of coral juveniles to SCTLD is urgently needed, to include different species, locations, parents, and algal symbionts, with the goals of assessing relative susceptibility and identifying potential sources of resilience for this critical life history stage.